Model Revitalisasi Pondok Kesehatan Desa (Ponkesdes) dan Pos Pembinaan Terpadu (Posbindu) untuk Promosi Kesehatan dan Deteksi Dini Faktor Risiko Penyakit Jantung di Desa Sepanjang Kecamatan Gondanglegi Kabupaten Malang - Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2019)
This study aims to develop a model for revitalizing community based health care intervention for strengthening cardiovascular diseases preventive services. The case of CBHI in Sepanjang village was used to test whether the proposed model is suitable implemented. The findings show that the model was effectively implemented as indicated by the full acceptance of health workers and voluntary health workers as well as the effectiveness of screening and health promotion intervention.